Environmental, Social, Governance (ESG) Sebagai Upaya Perusahaan Berkelanjutan Di Tahu Sehat Sari Klaten: Environmental, Social, Governance - Tamara Ayu Mustika (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
The implementation of Environmental, Social, and Governance (ESG) systems in companies has become a key focus to achieve long-term sustainability and enhance reputation in the eyes of stakeholders. ESG is a framework that helps companies integrate environmental, social, and governance considerations into their business operations. This research explores how ESG implementation can strengthen corporate performance by reducing environmental impacts through waste management and energy efficiency, improving social welfare through employee well-being and corporate social responsibility, and ensuring good governance through transparency and accountability. Case studies from known companies show that the integration of ESG principles not only meets regulatory demands but also creates added value for the company and society. By implementing ESG, companies can ensure sustainable operations, improve relationships with stakeholders, and achieve inclusive and sustainable growth.